An Implementation Assessment of Corporate Environmental Disclosure: An Empirical Study of CAC 40 Listed Companies - Ahmadi, Ali; Bouri, Abdelfettah (Journal of Environmental Accounting and Management, 2026)
The environmental accounting is an important tool for understanding the role played by the natural environment in the economy. Based on a content analysis approach this paper aims to understand the potential effect of some environmental attributes and financial characteristics on corporate environmental disclosure. Content analyses had been carried out on the 2013-2015 annual reports of the leading French firms Listed on CAC 40. The Research results that indicate that the environmental disclosure is positively associated to environmental attributes such as a low amount of hazardous waste, the voluntary adoption of environmental initiatives. Financial attributes, such as firm size, the need for capital, profitability and capital spending, are positively associated with environmental disclosure quality.